2022
DOI: 10.3899/jrheum.220386
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Specific Differences in Patients With Psoriatic Arthritis: A Systematic Review

Abstract: ObjectiveA systematic review of published literature was conducted to collate evidence on sex-specific differences in clinical characteristics, disease activity and patient-reported outcomes (PROs) in psoriatic arthritis (PsA), including response to treatment.MethodsSearches of MEDLINE, Embase and the Cochrane Database of Systematic Reviews were performed in November 2020 for observational studies of adults with PsA reporting outcomes by sex (published 2015–), with hand searches of systematic literature review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
(77 reference statements)
3
13
0
4
Order By: Relevance
“…The present article showed a worse psoriasis in males when compared to females in two PsA settings. This result has been previously reported [11], confirming that psoriasis could be more frequent in males. However, when evaluating the role of psoriasis in terms of disease burden, we found that psoriasis was a factor potentially influencing the PtGA, reinforcing that PtGA is able to capture differences between males and females when the skin involvement is present.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The present article showed a worse psoriasis in males when compared to females in two PsA settings. This result has been previously reported [11], confirming that psoriasis could be more frequent in males. However, when evaluating the role of psoriasis in terms of disease burden, we found that psoriasis was a factor potentially influencing the PtGA, reinforcing that PtGA is able to capture differences between males and females when the skin involvement is present.…”
Section: Discussionsupporting
confidence: 90%
“…Beyond the real possibility to achieve good disease control in PsA patients, evidence suggests a different burden of disease and response to treatment between sexes in patients with spondyloarthritis [7][8][9] and PsA [10][11][12]. Although PsA is considered equal in prevalence between males and females, evidence showed that the burden of the disease is higher in females when compared to males [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sex differences in the disease manifestation of PsA have been identified. 6,7 Women have significantly more peripheral arthritis and more frequently experience polyarticular involvement, whereas the oligoarticular pattern is more common in men. 8 Furthermore, women may be more prone to enthesitis and have higher tender joint counts, whereas men more commonly have axial involvement, severe psoriasis, and radiographic joint damage.…”
Section: Introductionmentioning
confidence: 99%
“…8 Furthermore, women may be more prone to enthesitis and have higher tender joint counts, whereas men more commonly have axial involvement, severe psoriasis, and radiographic joint damage. 6,7 Moreover, women frequently report greater pain, functional limitations, depression, and poorer quality of life. 7 Sex differences may also extend to molecular pathways related to disease development; one study suggested that the expression of genetic risk factors associated with disease susceptibility could vary with sex.…”
Section: Introductionmentioning
confidence: 99%